EFFECT OF FEDERAL GOVERNMENT'S RECURRENT EXPENDITURES ON ECONOMIC GROWTH OF NIGERIA (Journal of Contemporary Issues in Accounting, 2024)
The study investigated the effect of federal government’s recurrent expenditures on economic growth of Nigeria (1993 – 2023). The specific objective was to determine the effect of administration expenditure, economic services expenditure, social community service expenditure and transfers expenditure on the real gross domestic product of Nigeria. The study employed ex-post facto research design. The instrument for data collection was the Nigerian Bureau of Statistics and Central Bank of Nigeria (CBN) statistical bulletin from which relevant time series data covering the period 1993 to 2023 were obtained.Top of Form Ordinary Least Square simple regression model was used to test the hypothesis at 5% level of significance. The findings show that: administration expenditure has a positive but non-significant effect on the real GDP of Nigeria (p-value = 0.3169); economic services expenditure has a positive but non-significant effect on the real GDP of Nigeria (p-value = 0.5452); social community service expenditure has a positive but non-significant effect on the real GDP of Nigeria (p-value = 0.1531); transfers expenditure has a significant negative effect on the real GDP of Nigeria (p-value = 0.0047). In conclusion, direct public recurrent spending in enhancing the growth of the economy while promoting productivity. We recommend that the Ministry of Finance and Budget Planning should increase and ensure efficient allocation of funds to administrative functions to enhance public service delivery and governance; the Federal Ministry of Transportation should prioritize and increase investment in transportation infrastructure projects by improving transportation networks; the Federal Ministry of Education and Health should allocate more resources to education and healthcare sectors; the National Assembly and Ministry of Finance should review and rationalize transfer payments to ensure they are efficient and do not create economic distortions or dependency.
Keywords: Administration Expenditure; Economic Growth; Economic Services Expenditure; Federal Government’s Recurrent Expenditures; Real Gross Domestic Product; Social Community Service Expenditure; Transfers Expenditure